Comparison and analyses of differences in flexibility among top-level male and female handball players of different ages - Gruic, I.; Ohnjec, K.; Vuleta, D. (Facta Universitatis: Series Physical Education and Sport, 2011)
A battery comprised of 10 tests estimating global (sit and reach) and topologically defined flexibility (over-arm flip, hip flexion, extension and abduction), was assessed on the sample of subjects represented by a 38 male (24 junior and 14 senior) handball players and 34 female (18 junior and 16 senior) handball players, with the aim of determining the differences in general and local flexibility, with regard to the competition age of the subjects. The results of the analyses of differences (t-test) showed that statistically significant differences between junior and senior male team handball players were determined in the variables estimating flexibility of the shoulders and related body zone (MFLIP - over-arm flip), hamstrings (MFLPLL and MFLPLD) and flexibility of m. quadriceps and part of pelvic region (MFLZLL - hip extension of the left leg while lying face down, and MFLZLD - hip extension of the right leg while lying face down). Statistically significant differences were noted between junior and senior female handball players in the variables estimating flexibility of the lower back with related body zone (MFLSAR - seat and reach), hamstrings (MFLPLL - hip flexion of the left leg while lying in a supine position, and MFLPLD - hip flexion of the right leg while lying in a supine position).